Diagnostic accuracy of transcutaneous bilirubinometer as non invasive method to measure bilirubin in neonates - Anurag Yadav; Golla Anmol Manaswini Yadav; Malathi Mala (Al Ameen Medical College, 2021)
Background: The use of non-invasive, transcutaneous bilirubin monitoring (QTcB) as a jaundice screening in full-term infants is a well-established practice; however, there is a paucity of research in evaluating the use of QTcB in comparison with serum total bilirubin (TSB). The aim of the study is to assess the concordance between transcutaneous bilirubin and serum bilirubin in neonates with physiological jaundice and determine the utility of transcutaneous bilirubinometry in the management of physiological jaundice. Method: It is a cross-sectional observational study conducted at the Biochemistry department of tertiary care hospital, Mangalore over a period of 6 months with approval of the institutional ethics committee. All the newborn delivered by normal vaginal delivery were included for the study after obtaining the written informed consent from the parents. They were assessed for the hyperbilirubinemia by quantification of the serum bilirubin (Diazo method) and also transcutaneous bilirubinometer (BILIPROBE, MBJ20 at 450nm & 550nm wavelenght) testing on the forehead and sternum within the 10mins of blood collection for the serum bilirubin estimation. This was done at around 72hrs of birth as a pre-discharge screening of neonates. Results: Overall, 620 neonates were screened in the study of which 498 babies were assessed for eligibility, a total of 299 neonates were finally enrolled. QTcB and TSB measurements were taken and were correlating significantly with good strength of association (p<.001) with the sternum and forehead location. ROC curve for prediction of TSB and QTcB with cut-off index was 93.67% serum bilirubin, 89.6% at the sternum and 82.25% at the forehead. Conclusion: QTcB correlates closely with TSB concentration in neonates with full-term gestational age. The rate of rising in TcB may help in identification of neonates at risk and minimizing invasive blood investigations.